Letter : S.S. Rio Miera to Santander - Thompson, J.
028-0108-001 CABLE CODES:- A.B.C 6th EDITION WESTERN UNION 5 LETTER BENTLEY COMPLETE PHRASE BENTLEY SECOND PHRASE and PRIVATE CO-OPERATIVE WHOLESALE SOCIETY Ltd. Exporters, Buying and Shipping Agents. Export Department, 1, Balloon Street, Manchester, 4. IMPORTANT PLEASE ADDRESS CORRES INVOICES ETC EXPORT REF: ST/MM. TELEGRAPHIC ADDRESS: "WHOLESALE, MANCHESTER" TELEPHONE NO.: BLACKFRIARS 1212. 12th January, 1937. National Council of Labour, Transport House, Smith Square, London. S.W.1. Dear Sirs, s.s. RIO MIERA to Santander. We have received your letter of the 11th instant reference WMC/HVT/FC/406 and wish to express our thanks for your cheque value £37.10.0d. enclosed. Our official receipt is attached hereto. Yours faithfully, J. Thompson, Export Department. P.S. Our Bank Department will be sending the receipt to you direct. 292/946/28/108